The Opportunities of Working in a Challenging Environment - Ameha Atnafu Muluneh (Perspectives of Earth and Space Scientists)
Abstract A few days after the American Geophysical Union announced that I am the recipient of the 2020 Africa Award for research excellence in Earth or Ocean Sciences, I received an email from Michael Wysession, editor‐in‐chief of Perspectives of Earth and Space Scientists, to write a story about my scientific experiences. I was filled with emotions. I never thought of sharing my experience with other people (except to my wife and children and close friends). I hope my story will inspire mainly marginal students, who may think that society will exclude them owing to western credentials, and believe that they cannot achieve a spot in science because of their grades. I strongly believe that scientific excellence is achieved by hard work (mostly in a subject area that you like), and a little bit of good luck.